Production and Characterization of Non-Isocyanate Polyurethane/SiO2 Films Through a Sol-Gel Process for Thermal Insulation Applications - Noriega, Natalia (2019)
The reaction of cyclic carbonates with amines is the most attractive among the synthesis methods for isocyanate-free polyurethane. Non-isocyanate polyurethane films with SiO2 NPs fabricated by a sol-gel process are reported, where cyclic carbonates (CC) were produced under mild conditions by CO2 insertion in an epoxide complex in the presence of LiCl. A reaction of CC and polyamines was carried out in a low concentration polymer matrix of PVA. The materials were characterized by 1H-NMR, FTIR, UV-Vis, SEM, TGA, DTG, and a KD2 pro technique. polymer FTIR results are consistent with the literature, even with the use of a non-conventional methodology, where the found chemical interactions values were 3330, 2930 and 1637 cm 1. There are di erences in the polymers’ morphologies due to the presence and absence of SiO2 NPs according to SEM, where the spherical morphology and homogenous particle size distribution of NPs around 100 nm. According to TGA results, all polymers showed their last stage decomposition after 300 C and polymers with higher concentration of NPs showed even better stability. Due to the obtained results, the polymers have the potential to be used for thermal insulation without negative e ect on the environment.